1986
DOI: 10.1038/320063a0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transplantation in sheep embryos

Abstract: Nuclear transplantation and cell fusion techniques have proved valuable for embryological studies in several non-mammalian animal species. More recently these procedures have been used successfully in small laboratory mammals, notably the mouse, to investigate the ability of nuclei and cytoplasm from various sources to produce viable embryos when combined. The use of a similar approach to study the developmental biology of large domestic animals presents a number of technical and practical difficulties, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
261
2
11

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 691 publications
(277 citation statements)
references
References 10 publications
3
261
2
11
Order By: Relevance
“…Furthermore, blastocysts and outgrowths with low or absent Oct4-GFP did not give rise to ES cells. Somatic and embryonic cell cloning experiments have shown that, compared with the metaphase II ooplasm, the zygotic cytoplasm is an inadequate host to the transplanted nucleus (McGrath and Solter 1984;Robl et al 1986;Willadsen 1986;Howlett et al 1987;Cheong et al 1993Cheong et al , 1994. It is generally assumed that reprogramming subsequent to activation is minor; therefore, much effort to improve clone development has focused on the metaphase II ooplasm (Sun and Moor 1995;DiBerardino 1997;for review, see Solter 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blastocysts and outgrowths with low or absent Oct4-GFP did not give rise to ES cells. Somatic and embryonic cell cloning experiments have shown that, compared with the metaphase II ooplasm, the zygotic cytoplasm is an inadequate host to the transplanted nucleus (McGrath and Solter 1984;Robl et al 1986;Willadsen 1986;Howlett et al 1987;Cheong et al 1993Cheong et al , 1994. It is generally assumed that reprogramming subsequent to activation is minor; therefore, much effort to improve clone development has focused on the metaphase II ooplasm (Sun and Moor 1995;DiBerardino 1997;for review, see Solter 2000).…”
Section: Discussionmentioning
confidence: 99%
“…All clones were derived by nuclear transplantation using nuclei from blastomeres as donors (Willadsen, 1986;Prather et al, 1987Prather et al, , 1989. Importantly, these researchers used oocytes rather than zygotes as recipients.…”
Section: Mammalian Nuclear Transfer: Selected Highlightsmentioning
confidence: 99%
“…For normal development to proceed, it is crucial that, in a Briggs et al, 1952Briggs et al, 1962 Nuclear transfer-derived frogs Gurdon, 1962Gurdon, 1975 Rabbit nuclear transfer Bromhall, 1975Bromhall, 1979 Nuclear transplantation in fish Gasaryan et al, 1979Gasaryan et al, 1981 Derivation of mouse ES cells Evans and Kaufman, 1981;Martin, 1981Martin, 1983 Nuclear transplantation in the mouse Solter, 1983 1986 Lambs cloned from blastomeres Willadsen, 1986Willadsen, 1987 Cattle cloned from blastomeres Prather et al, 1987Prather et al, 1989 Pigs cloned from blastomeres Prather et al, 1989Prather et al, 1994 Calves cloned from ICM cells First, 1994 1996 Sheep cloned from embryonic cell line Campbell et al, 1996 First mammal cloned from adult cell (sheep "Dolly") Wilmut et al, 1997Wilmut et al, 1998 Derivation of human ES cells Thomson et al, 1998Thomson et al, 2000 Mouse nuclear transfer-derived ES cells Munsie et al, 2000Munsie et al, 2002 Terminally differentiated cells cloned Hochedlinger et al, 2002aHochedlinger et al, 2002 First therapeutic application in mice Rideout et al, 2002 a ES, embryonic stem; ICM, inner cell mass. This table summarizes a number of selected highlights starting from the first demonstration of the NT technique by Briggs and King to the first "proof of principle" study in mice showing the therapeutic potential of the technique.…”
Section: Nt Efficiencymentioning
confidence: 99%
“…The first scientist who successfully used cytoplasts produced by enucleation of metaphase II oocytes was Steen Willadsen [12]. In his experiments, blastomeres isolated from 8-cell stage embryos were fused to mature oocyte cytoplasts and several lambs were born.…”
Section: Birth Of Dollymentioning
confidence: 99%